2006
DOI: 10.5194/bg-3-439-2006
|View full text |Cite
|
Sign up to set email alerts
|

Photochemical production of ammonium in the oligotrophic Cyprus Gyre (Eastern Mediterranean)

Abstract: Abstract. We investigated the photoproduction of ammonium (NHPhotoammonification rates around local noon were 0.4-2.9 nmol L −1 h −1 . Normalised to time integrated irradiance, these rates were 0.9-3.8 pmol L −1 h −1 /(W m −2 ) and were significantly correlated with Chromophoric Dissolved Organic Matter (CDOM) absorbance at 300 nm normalised to Dissolved Organic Carbon (DOC). These results are consistent with the notion that successive CDOM photobleaching in the surface mixed layer results in decreased DOC-nor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 44 publications
2
23
1
Order By: Relevance
“…The minimum, maximum, average and standard deviation for all a 300 measurements were 0.17, 0.61, and 0.3 ± 0.2 m -1 , respectively. Values of a 300 were similar to those reported for the pelagic region of Atlantic Ocean and were slightly higher than values from the Cyprus gyre region (Kitidis et al 2006b). Absorption at 325 nm (minimum, maximum, average and standard deviation of 0.08, 0.40, and 0.20 ± 0.07 m -1 ) was significantly higher than values reported by Nelson et al (2007) Spectral slope values, calculated at wavelengths between 270 and 400 nm, were between 0.026 and 0.042 nm -1 with an average value of 0.033 ± 0.004 nm -1 .…”
Section: Cdom Optical Propertiessupporting
confidence: 74%
See 1 more Smart Citation
“…The minimum, maximum, average and standard deviation for all a 300 measurements were 0.17, 0.61, and 0.3 ± 0.2 m -1 , respectively. Values of a 300 were similar to those reported for the pelagic region of Atlantic Ocean and were slightly higher than values from the Cyprus gyre region (Kitidis et al 2006b). Absorption at 325 nm (minimum, maximum, average and standard deviation of 0.08, 0.40, and 0.20 ± 0.07 m -1 ) was significantly higher than values reported by Nelson et al (2007) Spectral slope values, calculated at wavelengths between 270 and 400 nm, were between 0.026 and 0.042 nm -1 with an average value of 0.033 ± 0.004 nm -1 .…”
Section: Cdom Optical Propertiessupporting
confidence: 74%
“…In the Mediterranean Sea, only limited CDOM data are available (Seritti et al 1998;Babin et al 2003;Vignudelli et al 2004;Kitidis et al 2006b) and the bio-optical properties of CDOM are not well understood. The Eastern Mediterranean is dominated by ultra-oligotrophic waters and has a higher coastline/volume ratio than most ocean waters.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang and Anastasio [2003] also reported production of NH + 4 from the photolysis of aerosol organic nitrogen, which may involve deamination of amino acids [Milne and Zika, 1993]. In seawater, the production of NH x (sw) from the photolysis of DON has been demonstrated in many regions of the ocean [Bushaw et al, 1996;Morell and Corredor, 2001;Kitidis et al, 2006;Aarnos et al, 2012;Xie et al, 2012;Rain-Franco et al, 2014] [e.g., Norman and Leck, 2005] in different seasons are needed to further our understanding of the budget of atmospheric reduced nitrogen in the marine atmosphere.…”
Section: Comparison With Atmospheric Observationsmentioning
confidence: 99%
“…For example, the greatest rates of photoammonification in a boreal pond were observed in irradiated water collected shortly after spring thaw (Bushaw et al, 1996). Kitidis et al (2006) observed that photoammonification rates were significantly correlated with CDOM concentrations (as measured by absorbance at 300 nm normalized to DOC), and that photochemical NH 3 production decreased as photobleaching progressed. These results suggest that photoammonification may be greatest for CDOM with little prior exposure to sunlight (Bushaw et al, 1996).…”
Section: Introductionmentioning
confidence: 94%